Insights from the EXPOSITION Study: Exposome-related microRNA Expression and Clinical Outcomes in People with multiple sclerosis (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionMicroRNAs (miRNAs) are emerging as promising biomarkers of neuroinflammation and may capture the influence of lifestyle and environmental exposures in people with multiple sclerosis (pwMS). The EXPOSITION study[1] aims to elucidate relationships between internal exposome markers including miRNA profiles and clinical, demographic, and lifestyle factors in pwMS.Objective(s)                                               To assess the associations between the relative expression of five candidate miRNAs and clinical, demographic, and lifestyle variables, with a particular focus on the exposome and functional and psychological outcomes in pwMS.MethdsIn this cross-sectional analysis, we included 139 pwMS (median age 45 years [IQR: 35–56], 65% female) from the provinces of Pavia and Milan in the Lombardy region of Italy. Relative expression levels of five candidate miRNAs (mir30, mir146, mir330, mir574, mir664) were quantified and compared across clinical and lifestyle categorical variables groups using the Mann-Whitney U test (for binary variables) or the Kruskal-Wallis test (for variables with more than two categories). Spearman correlation analyses were conducted to assess the relationship between each miRNA and continuous variables, including age, BMI, EDSS, dietary inflammatory index, and quality of life scores.ResultsThere were no statistically significant differences in microRNA expression between EDSS disability groups or across most clinical or lifestyle variables. Notably, mir146 expression was significantly higher in participants with a pro-inflammatory dietary pattern compared to those with an anti-inflammatory pattern (p = 0.0187), and mir146 was positively correlated with the mental health component of the quality of life MSQoL-29 questionnaire (rho = 0.336, p = 0.0174) [Table 1]. In contrast, higher disability status (EDSS >4) was significantly associated with older age (median 51 vs. 44 years, p = 0.047), more frequent prior relapses (94% vs. 69%, p = 0.040), and lower physical (p = 0.039) and mental (p = 0.034) quality of life. Significant group differences were also observed for MS type (p = 0.008), MS stage (p = 0.034), and occupational status (p = 0.063, trend) between the two EDSS groups. No significant associations were identified between disability status and microRNA expression, diet category, physical activity, or MRI lesion status.ConclusionsIn this preliminary analysis, higher disability among pwMS was more strongly linked to clinical history, age, and quality of life than to lifestyle factors or circulating miRNA levels. Mir146 may act as a molecular intermediary between dietary inflammation, mental health, and neuroinflammatory processes in MS. These findings highlight the need for replication and longitudinal validation in larger, independent cohorts.